Time-dependent biphasic alterations in brain metabolism following chronic ketamine exposure in mice - Lim, Seo-Hyun; Choi, Young-Suk; Kim, Eosu; Kim, Chul Hoon; Song, Ho-Taek (Frontiers in Pharmacology, 2025)
BackgroundKetamine has attracted clinical interest for its therapeutic potential, but prolonged exposure raises concerns about dependence and its long-term effects on brain metabolism.Materials and MethodsMale mice received daily intraperitoneal injections of ketamine (30 mg/kg) for 28 days. Brain glucose metabolism was evaluated using [18F]FDG positron emission tomography at 1 h, 1 week, and 1 month post-injection. Expression levels of glucose transporters (GLUT1), glycolytic enzymes (PKM2, HK1), NMDA receptor subunits (NR2B), and apoptotic markers (caspase-3) were analyzed by Western blotting and RT-PCR.ResultsFDG-PET imaging suggested a biphasic metabolic pattern, with an increase in uptake at 1 h and 1 week, followed by a significant reduction by 1 month, returning toward baseline levels. GLUT1 mRNA expression gradually increased, although protein levels did not show a clear parallel change. PKM2 and HK1 remained largely unchanged. At 1 month, NR2B and caspase-3 transcripts were elevated, while protein-level changes were less evident, suggesting possible transcriptional regulation of stress-related pathways.DiscussionThese findings demonstrate that ketamine induces dynamic alterations in brain glucose metabolism accompanied by molecular adaptations. The early hypermetabolic response may reflect acute excitatory effects, whereas longer exposure could engage compensatory or stress-associated mechanisms. Metabolic imaging may provide a useful, non-invasive approach to better understand ketamine’s temporal effects and support long-term safety monitoring.